Platelets support a protective immune response to LCMV by preventing splenic necrosis - David Loria, Gilbert (2013)
Severe arenaviral infections in humans are characterized by clinical findings common to other viral hemorrhagic fevers (VHFs), including thrombocytopenia, leukopenia, skin and internal organ hemorrhages, high viral replication, splenic necrosis, and death. Host responses, rather than direct damage by the arenaviral replication, account for most of the observed pathology, but it is not known what protective roles platelets may have in each of the manifestations. To address this issue in an animal model, we compared nondepleted (100%), partially depleted (15%), and profoundly (< 2.5%) platelet-depletedmice infected with the mouse arenavirus lymphocytic choriomeningitis virus (LCMV). Here, we describe that systemic bleedings and death were seen only in those animals receiving the stronger depletion treatment. Furthermore, we showed that the nonhemorrhagic but partially platelet-depleted mice were unable to control the viral replication because of generalized splenic necrosis, affecting innate and adaptive immune cells. These data suggest that, by their supportive roles in hemostasis, platelets may be preventing the severe pathology observed in human arenaviral infections.